Printed catalogues of booksellers as a source for the history of the book trade - Christian Coppens; Angela Nuovo (JLIS.it, 2018)
Printed advertisements and lists of books for sales were used by publishers and booksellers in the fifteenth and sixteenth centuries respectively to promote and increase the sale of books in distant markets. This article proposes an overall interpretation of the uses of these catalogues in the trade in books, the purposes they were designed to fulfil, and the reading public(s) they aimed to reach. Specific attention is paid to the book prices which are found in about 30% of the surviving printed catalogues. These represent a reliable testimony to the pricing policies some of the most important publishing firms, and the segments of the market they intended to serve. The catalogues are therefore among the main sources for our understanding of the mechanisms of the early modern book trade and its economic structure.